(untitled) (International Journal of Pharmaceutical Sciences and Drug Research, 2025)
The present study evaluated that anti-obesity potential of a formulation. As obesity is chronic metabolic condition and leads to various co-morbidities hence there is need to find out herbal promising treatment with maximum potential and minimum side effects. Marketed allopathic drugs have side effects hence here is switch to herbal treatment. Obesity was triggered via subcutaneous administration of progesterone over a 28-day period, during which both a polyherbal formulation and a standard treatment were given. Essential physical measurements were documented, along with serum parameters such as total cholesterol, triglycerides, LDL, HDL, and VLDL. Moreover, liver function enzymes (SGPT and SGOT) and glucose levels were evaluated, and a histopathological analysis of adipose tissue was conducted. The results demonstrated that the polyherbal formulation significantly reduced obesity-related parameters such as VLDL, total cholesterol, HDL, triglycerides, LDL in treatment group. These findings suggest that the polyherbal formulation effectively counteracts progesterone-induced obesity.